BENTUK PERMINTAAN SOPAN DALAM BAHASA INGGRIS DAN BAHASA WAYOLI: SUATU ANALISIS KONTRASTIF - Kotu, Ignasextepanus (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This Skripsi is entitled â€œBentuk Permintaan Sopan dalam Bahasa Inggris dan Bahasa Wayoli : Suatu Analisis Kontrastifâ€. The problem of this research is how the forms of polite request in English and Wayoli LanguageÂ and how to use the forms. The research questions to be answered are what are the forms of polite request in English and Wayoli Language and what are the similarities and differences of both languages. In terms of methodology, the writer used descriptive method and contrastive analysis. The whole data were collected by doing library and field research. The data of both languages were analyzed based on Ladoâ€™s (1971) theory. The results of this research show that the polite request in English and Wayoli language have some similarities and differences. Both languages have polite form. Besides that, the differences in both languages are found in terms of structure, forms of sentences, distribution of verbs and personal pronouns which were used to address the hearers. Â Key Words: Polite Request in English and Wayoli Language, Contrastive Analysis.